Bioinformatics-based prognostic value and in vitro functional validation of PTK6 in cutaneous melanoma - Niu, Yanyan; Liu, Xiaoyu; Shi, Aixiu; Tang, Danli; Yao, Xiaodong; Lu, Yan (Frontiers in Oncology, 2025)
BackgroundCutaneous melanoma (CM) is a highly malignant tumor originating from melanocytes. Rising incidence rates pose a significant burden on global health and economy. Advanced CM patients face poor prognosis due to high recurrence and treatment resistance. Identifying new prognostic biomarkers and therapeutic targets is crucial for personalized interventions. This study focused on protein tyrosine kinase 6 (PTK6), whose role in CM remains unclear.MethodsTo overcome these limitations, this study focused on PTK6 and integrated CM transcriptomic and clinical data from TCGA and GEO databases. Bioinformatics analysis evaluated PTK6 expression and its impact on prognosis. GO and KEGG analyses explored biological functions of PTK6-related differentially expressed genes (DEGs). A prognostic risk score model was constructed and validated based on DEGs, and immune cell infiltration, tumor mutation burden (TMB), chemotherapy drug sensitivity, and immunotherapy response were analyzed. Additionally, regulatory mechanisms of PTK6 were explored through mRNA-miRNA-lncRNA and protein interaction networks. Furthermore, in vitro experiments validated PTK6's biological functions.ResultsThe results showed that PTK6 was significantly upregulated in CM, and its high expression was closely associated with a decreased overall survival of patients. Enrichment analysis suggested that PTK6-related differentially expressed genes were mainly involved in epidermal development, keratinocyte differentiation, and the IL-17 signaling pathway. The prognostic model constructed based on 11 characteristic genes could effectively distinguish between high- and low-risk patients, showing improvements in prognostic accuracy. Patients in the high-risk group had significantly worse prognosis and higher TMB levels. The low-risk group was more sensitive to various chemotherapy drugs, and most immune checkpoint genes were negatively correlated with prognostic genes. TIDE analysis showed that patients in the high-risk group had a higher potential responsiveness to immunotherapy. Regulatory network analysis identified key miRNAs, lncRNAs, and transcription factors related to PTK6. In vitro experiments further confirmed that high expression of PTK6 promoted the proliferation, invasion, and migration of melanoma cells, and its enzymatic active site played an important regulatory role in the above functions.ConclusionThe experimental results demonstrate that PTK6 is a novel prognostic biomarker and potential therapeutic target for CM, highlighting its strong potential for real-world clinical applications.This study provides a theoretical basis for understanding PTK6's role in CM and its application in personalized treatment. However, further large-scale, multi-center studies are needed to verify its mechanistic role and clinical value.